Barriers and facilitators to implementing comprehensive sex education in Texas public schools: A qualitative study. - Lauren Holt; Sarah Janek; Gavin Yamey (PLoS ONE)
Introduction In Texas, the adolescent birth rate is higher than the national average and STIs have steadily increased over the last decade. Sex education is not mandated in Texas and the majority of public schools provide an abstinence-based sex education. Comprehensive sexuality education (CSE) programs are widely endorsed by national and global health organizations and research has shown that they are more effective in reducing poor sexual health outcomes than abstinence-based programs. The purpose of this study is to identify barriers and facilitators to implementing CSE at local and state levels in Texas. Methods Qualitative study design consisting of ten semi-structured interviews with eleven key informants (n = 11) conducted in 2021. Results Three barriers- ideological opposition to CSE, discrimination against LGBTQ+ people, myths and misconceptions about CSE- and two facilitators- champions, collaboration with community stakeholders- to implementing CSE policy were identified. Conclusion Study findings provide insight into the opposition faced by sex education advocates, which often stems from myths and misperceptions of CSE content and the stigmatization of sexual and gender minoritized groups. Parents, youth, medical professionals, and academic researchers are instrumental in dispelling sex education myths and misperceptions and engaging with community stakeholders.